Analysis of The Influence of Automotive Brand Purchasing Intentions In Batam City - Tjoa, Kevin; Saputra, Suyono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This research aims to identify the influence of brand trust attitudes, brand image, risk perception, word of mouth promotion, brand awareness, and brand trust on automotive brand purchase intentions. Methodology/approach – This research aims to test hypotheses using quantitative research methods based on the philosophy of positivism. Data was collected from automotive brand buyers in Batam City using questionnaires as the main data collection tool, as well as literature studies to support relevant information. Findings – Attitude does not significantly influence purchase intentions when purchasing automotive brands (p-value > 0.05), but plays an important role in increasing trust (p-value=0.000). Brand awareness and brand image have a significant positive impact on purchase intention (p-value=0.000), indicating that good brand recognition and image increase purchase intention. In contrast, perceived risk does not influence purchase intention. Even though trust has no effect, word of mouth has a significant positive impact on purchase intentions, indicating that brand reputation in society influences consumers' purchase intentions. Novelty/value – This research significantly contributes to the understanding of the factors that influence consumer purchasing decisions in the context of automotive brands. The conclusion shows that attitude has a key role in building consumer trust in automotive brands, while brand awareness and brand image have a significant positive impact on purchase intentions. The research results also highlight the importance of word of mouth in shaping purchase intentions, with perceived risk not playing a significant role in consumers' purchase decisions. The practical implications of these findings can help automotive companies design more effective marketing strategies.